Key opinion leaders: influencers of the digital age / Efina Hamdan and Siti Nur Fadzilah Abdullah - Hamdan, Efina; Abdullah, Siti Nur Fadzilah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In the fast-paced digital era where information spreads at lightning speed and opinions are formed and reshaped within moments, the role of Key Opinion Leaders (KOLs) has become increasingly prominent. KOLs are individuals who possess expertise and influence in a specific field and have the power to shape public opinion, consumer behavior and even policy decisions. KOLs stand out from other influencers due to their profound knowledge and authority in their respective domains. Whether it’s in fashion, technology, fitness or any other industry, KOLs possess an extensive understanding and experience that enables them to offer valuable insights and guidance. Their expertise is often built over years of experience, education, research and practical application, establishing them as trusted sources of information. While KOLs and influencers may share certain similarities, the key distinction lies in the source of their influence and the nature of their content. KOLs derive influence from their specialized knowledge and expertise, providing valuable insights and guidance within the field. Conversely, influencers leverage their personal brand, relatability and entertaining content to connect with and engage their audience, often focusing on lifestyle and popular culture. Understanding these differences is crucial when designing marketing strategies or seeking out individuals who align with specific goals and objectives.